Adopting BIM Technology in Fall Prevention Plans - Hayder Razzaq Abed; Wadhah A. Hatem; Nidal A. Jasim (Civil Engineering Journal, 2019)
Building Information Modeling is a modern technique that has contributed in improvement of construction industries. Early detection of hazards during the life cycle of the project will contribute to protect the working environment from exposure to risks that will affect the time and cost. The changing nature of the sites makes it difficult in identifying the fall risks accurately. Based on BIM 4D simulation, the objective of this study is to create a computer model by using BIM technology to help accurately determine (a) the hazards of falling from the edges (b) the hazards from struck by falling objects, by relying on the opinions of safety experts in identifying potential risks and demonstrating the effectiveness of this technique in facilitating hazards acknowledgment. In this research, Iraqi safety rules and safety rules of OSHA were adopted. The research idea was applied to a school building project under construction as a case study to benefit from the research outputs in improving the safety of school’s buildings projects. The results displayed that the model prepared by the researchers helped the safety managers in understanding the details and sequence of work easily, thus contributed to the precise identification of the falling hazards, use suitable safety equipment for each risk, in addition to the possibility of using this model as a training program for workers in the workplace to help give an idea of the nature of risk which they may be exposed it, increase safety communication and generate time schedule empty from risks. Safety managers believe that this model can contribute to improve workplaces safety and prevent time and cost losses due to reliance on inaccurate methods based on static 2D schemes and sense in risk identification.